2004
DOI: 10.1590/s0100-204x2004001200009
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre mapas de solos obtidos por sensoriamento remoto espectral e pelo método convencional

Abstract: Resumo -O meio científico carece de métodos que efetivem a utilização da espectroradiometria em mapeamentos de solos. O objetivo deste trabalho foi comparar o uso do sensoriamento remoto espectral com o método convencional, na obtenção de mapas de solos. Utilizando o mapa planialtimétrico como base, trinta pontos de amostragem foram demarcados na área de estudo. As amostras foram coletadas a 0-20, 40-60 e 80-100 cm de profundidade em cada ponto, todos georreferenciados, totalizando noventa amostras nas quais f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
1
13
0
7
Order By: Relevance
“…In the evaluation of the maps produced by DSM, most authors take a single conventional soil map as reference, for a same legend (for example Chagas et al, 2011;Nolasco-Carvalho et al, 2009;Behrens et al, 2005;Demattê et al, 2004). However, conventional maps differ according to the soil scientist that constructed it, since their establishment includes both science and art (Soil Survey Staff, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In the evaluation of the maps produced by DSM, most authors take a single conventional soil map as reference, for a same legend (for example Chagas et al, 2011;Nolasco-Carvalho et al, 2009;Behrens et al, 2005;Demattê et al, 2004). However, conventional maps differ according to the soil scientist that constructed it, since their establishment includes both science and art (Soil Survey Staff, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The sum of bases (SB), cation exchange capacity (CEC), and base saturation (V) showed the following values for R 2 : 0.44, 0.46, and 0.29, respectively, in contrast with Nanni and Demattê (2001), Dunn et al (2002), and Demattê et al (2004a), who found values of R 2 greater than 0.74 for these properties. However, such properties often show coefficients with values lower than 50 % (Demattê and Garcia, 1999).…”
Section: Quantification Of Soil Propertiesmentioning
confidence: 85%
“…In fact, this led Demattê et al (2004a) to use a spectroscopy information to aid in pedological mapping. Afterwards, Fiorio et al (2014) suggest the use of spectral sensors for the aid of field work in pedological maps.…”
Section: Resumo: Múltiplas Ferramentas Tecnológicas No Mapeamento Digmentioning
confidence: 99%
See 2 more Smart Citations